DNA/BSA binding interactions and VHPO mimicking potential of vanadium(IV) complexes: Synthesis, structural characterization and DFT studies. (30th October 2017) - Neelakantan, M.A.; Balakrishnan, Chithiraivel; Selvarani, V.; Theetharappan, M.
Abstract : Vanadium(IV) Schiff base complexes (VOL 1 ‐VOL 3 ) were synthesized and characterized by elemental analysis, various spectral methods and single crystal XRD studies. Structural analysis of VOL 2 reveals that the central vanadium ion in the complex is six coordinate with distorted octahedral geometry. Density functional theory (DFT) and time dependent (TD‐DFT) studies were used to understand the electronic transitions observed in the complexes in UV–Vis spectra. The electrochemical behavior of the complexes was investigated in acetonitrile medium exhibit quasi‐reversible one electron transfer. The DNA and BSA protein binding interaction of vanadium complexes has been explored by UV–Vis and fluorescence spectral methods and viscosity measurements reveal that the complexes interact with CT‐DNA through intercalation mode and follows the order VOL 1  < VOL 3  < VOL 2 . The complexes exhibit binding interactions with BSA protein. The complexes act as chemical nuclease and cleave DNA in the presence of H2 O2 . The 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) assay was used to evaluate the radical scavenging activity demonstrate the antioxidant property of the complexes. The antimicrobial activity was screened for several microorganisms, Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli . The mimicking of vanadium haloperoxidase was investigated by the bromination of the organic substrate phenol red by vanadium complexes in the presence of bromide and H2 O2 . Abstract : Vanadium(IV) Schiff base complexes (VOL 1 ‐VOL 3 ) was synthesized and characterized by various spectral methods and single crystal XRD studies. The VHOP mimicking activity of vanadium complexes was investigated.